CP-017 Efficacy and safety of nivolumab in a tertiary hospital: early access programme. (25th February 2017) - Fontela, C; Miguel, M de; Etxeberria, M; Fernandez, J; Sanchez, M; Iruin, A; Miguel, R San; Larrea, N; Sarobe, M
Abstract : Background: Nivolumab is approved by the US Food and Drug Administration for the treatment of patients with melanoma, metastatic non-small cell lung cancer (NSCLC) and renal cell carcinoma (RCC), and has been included in our hospital's formulary since 2015. Purpose: To evaluate the efficacy and safety of patients treated with nivolumab in our hospital in real world data. Material and methods: This was a retrospective observational study of all patients included in the nivolumab early access programme (November 2015–February 2016). Measured variables included: age, sex, diagnosis, disease stage, ECOG, number of cycles, prior lines of treatment, objective response and adverse effects. Evaluation of the response was performed according to RECIST version 1.1, and toxicity as defined by the NCI-CTCAE, version 4.0. Results: 8 patients were included (7 men), median age 68.5 years (52–74) and ECOG 1–2. Nivolumab candidates were treated with 3 mg/kg intravenous infusions every 14 days. 6 patients were diagnosed with lung cancer (2 squamous histology, 4 adenocarcinomas) and 2 other patients had RCC. All patients had stage IV disease except one who had stage IIIA disease. They had previously received a median of two lines of treatment and the median number of cycles administered was 6. All patients with NSCLC had progressed after platinum based chemotherapy and 4 had been treated with docetaxel. Patients with RCC had received TKI therapy and everolimus previously. Regarding effectiveness, no patient obtained an objective response (complete response+partial response), 4 patients (50%) maintained stable disease (SD), 2 patients are in progression (25%) and 2 patients are awaiting evaluation by imaging but with clinical improvement. Treatment related adverse effects of any grade were reported in all patients. The most common were asthenia, respiratory infection, hyporexia, nausea and anorexia. One patient required hospitalisation with colitis grade 3. Conclusion: The effectiveness in terms of objective response rate was lower than that reported in the literature. The tumour response rate was limited to SD. Treatment related adverse effects were similar to those described in other studies, mostly grades 1–2. To evaluate efficacy and long term safety, a longer monitoring period is required. It is essential to measure the health outcomes of new and expensive drugs to rationalise their use and optimise efficiency in the oncology area. References and/or acknowledgements: Brahmer J, et al. Nivolumab versus docetaxel in advanced squamous-cell non-small-cell lung cancer. N Engl J Med2015;373:123–35. No conflict of interest